High-Precision Target Detection of Remote Sensing Image Based on Feature Enhancement with 6G Technology - Haiyan Chen (Advances in Multimedia)
We provide remote sensing image enhancement technology based on 6G nursing urine technology to solve the main problems and current challenges of target detection in remote sensing imaging. High-resolution images: to get a good image, first look at the remote control image, and objective findings on the remote control image play an important role in this process. Military and civilian use: at present, many advanced object detection algorithms have achieved success in natural imaging, but their development is limited by two factors: large variation in object size and low detection accuracy, the scale, rotation direction, and distribution density of remote sensing images. On the other hand, the first remote sensing image is usually a high-resolution, large-scale image, which requires more time than blank image detection. The model is fine-tuned on the ICDAR2015 training package for 60,000 repetitions. The same model experimentally reduced the image to 1280 × 768 and displayed the results in one dimension. Therefore, in order to solve the problem of low detection due to changes in azimuth, rotation direction, and velocity distribution, it is necessary to further study methods for detecting large-capacity remote sensing objects using abundant high-precision remote sensing technologies, sensing imaging service on remote sensing maps.